Analisis Kesalahan Berbahasa dalam Berita Online “Makna Di Balik Keris Tidak Melulu Soal Hal Mistis” Kompas.com - Muhammad Maulana Yusuf; Muhammad Farhan (Populer: Jurnal Penelitian Mahasiswa, 2022)
Language has an important role in presenting sources of information and knowledge. One of the media used as a source of information is print media such as newspapers or newspapers. Newspapers are now not only in the form of print on paper, but many newspapers have created their own blogs or pages so that news can be read online. News has a characteristic, namely using straightforward language and writing systematics that are guided by the General Guidelines for Indonesian Spelling.